Pengawasan Pemerintah Daerah dalam Penyediaan Air Bersih oleh PDAM Kota Padang Panjang - Eka Putri, Mery; Permana, Iip (Policy, Law and Political Research Center, 2024)
This study analyzes empirically the Supervision of Local Government in the Provicion of Clean Water by PDAM Padang Panjang City. The data analysis thecnique using MAXQDA software application. This research uses qualitatif methods with a descriptive approach. With a location in Padang Panjang City. Data collected by interview and documentation. The results of this study indicate thet supervision is carried out by means of indirect supervision where the PDAM reports the results of its to the Regional Government.